LAW AND PUBLIC RELATIONS IN INDONESIA: VIEWED FROM THE THEORY OF JOHN HENRY MERRYMAN ON STRATEGIES OF LEGAL DEVELOPMENT - Djatmiko, Wahju Prijo (Walisongo Law Review (Walrev), 2019)
Principally, legal development is a sustainable development, its function  as human interest protection, legal aims to reach an order and balance. Order in society guarantees the protection on human interest.  Even though, the development on law is directed to create order in society, meaning law and society are interconnected, there are still plenty of legal products that are not able to meet people needs, and one of them is the judicial review on  the Act no. 19 year 2013 on Protection and Enforcement to Farmers. This  reflects that the Act does not represent social factors. This shows no harmony and benefit connections between the Act no.19 year 2013 as written legal product and society. This phenomenon, then, is analyzed from Theory of John Henry Merryman on Legal Development Strategy (Orthodox and Responsive). The process of making a responsive legal product is a participative one meaning that the process involves greatly the participation of society through social groups and individual in community. Reversely, orthodox legal product is characterized by its centralistic process in which state institutions dominate the process, especially  the authority of executives.